Removal of uranium from soil using full-sized washing electrokinetic separation equipment. (July 2015) - Kim, Gye-Nam; Kim, Seung-soo; Moon, Jei-Kwon; Hyun, Jae-hyuk
Highlights: 800 L washing-electrokinetic separation equipment was manufactured to remove uranium. The pH of cathode electrolyte solution was controlled 0.5–1.0 for the formation of UO 2+ . 60–65% of the uranium was removed from the soil by the soil washing equipment. The removal efficiency of uranium from the soil for 25 days was 96.7%. The removal efficiency of uranium from the soil for 35 days was 99.0%. Abstract: 800 L washing-electrokinetic soil separation equipment was manufactured to decontaminate uranium contaminated soils from Korean nuclear facilities. For the removal of uranium at more than 95% from radioactive soil through soil washing-electrokinetic technology, several decontamination experiments were carried out. For a reduction of the generation of large quantities of metal oxides in a cathode, a pH controller is used to control the pH of the electrolyte solution between 0.5 and 1.0 for the formation of UO 2+ . More than 60% metal oxides were removed through pre-washing, an electrolyte solution was circulated by a pump, and a metal oxide separator filtered the metal oxide particles. 60–65% of the uranium was removed from the soil by soil washing as a part of the pre-treatment. When the initial 238 U concentration of the soil was 22.2 Bq/g, the required electrokinetic separation time for the removal of below the clearance 238 U concentration of 0.4 Bq/g was 35 days, and the generated electrolyte solution rate was 1.4 ml/g. When the initial concentration of 238 U in the soil was higher, a longer decontamination time was needed, but the removal rate of 238 U from the soil was higher.